Liquid packaging adhesive as well as preparation method and application thereof
By using liquid packaging glue with vinyl silicone and acrylate modified polybutadiene and other components, the problem of degradation of perovskite solar cells in humid or high-temperature environments is solved, and efficient water vapor barrier and ultraviolet resistance is achieved, extending the service life of the battery and improving optical performance.
Patent Information
- Application Number
- CN202510034122.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-29
AI Technical Summary
Perovskite solar cells are prone to degradation in humid or high-temperature environments, resulting in degradation or failure of performance. The existing packaging films are under large stress during lamination, which may cause damage to perovskite materials and are sensitive to ultraviolet rays, affecting transparency and photoelectric conversion efficiency.
A liquid packaging glue is prepared by using vinyl silicone resin as the main resin, combined with acrylate modified polybutadiene, vinyl silicone oil and crosslinking agent and other components. The cured packaging glue film has excellent light transmittance, stability, mechanical strength and water vapor barrier properties.
Effectively extend the service life of perovskite batteries, improve the optical performance of the battery, resist moisture intrusion, improve the UV resistance and thermal stability of the adhesive film, and ensure the long-term and efficient operation of photovoltaic modules.
Smart Images

Figure CN119899632A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of packaging technology, and in particular to a liquid packaging adhesive and a preparation method and application thereof. Background Art
[0002] As a clean and renewable energy source, solar energy has attracted more and more attention from countries. The progress of photovoltaic technology has continuously improved the efficiency of solar cells and gradually reduced their costs, which has promoted the rapid development of the photovoltaic industry. The new generation of perovskite solar cells is gradually becoming the new favorite of the photovoltaic industry due to its high efficiency, low cost and easy manufacturing. However, the sensitivity of perovskite materials to the environment makes the requirements for packaging materials more stringent. The sensitivity of perovskite materials to the environment is mainly reflected in their fragility to humidity and oxygen, especially in humid or high temperature environments, which are easy to degrade, resulting in performance degradation or failure. Therefore, the selection of encapsulation film should not only meet basic protection requirements, such as moisture resistance, oxidation resistance and UV resistance, but also have excellent light transmittance and thermal stability to ensure the long-term and efficient operation of photovoltaic modules. In addition, the packaging material must also have good mechanical strength and flexibility to adapt to different application scenarios and environmental changes, thereby effectively extending the service life of perovskite cells.
[0003] In the solar cell industry, it is a common process to encapsulate and laminate EVA, POE, PVB and other types of adhesive films with backplane glass. However, the lamination temperature of these adhesive films is above 130°C, and the stress applied during lamination is large, which may damage the perovskite material. In addition, these adhesive films are highly sensitive to ultraviolet rays. Long-term exposure to sunlight may cause degradation and yellowing of the materials, affecting the transparency and photoelectric conversion efficiency of photovoltaic modules. In recent years, the application of organic silicone films in perovskite solar cells has gradually attracted attention because of its unique Si-O-Si structure with good flexibility, electrical insulation, UV resistance, high temperature resistance and moisture resistance, which can effectively protect perovskite cells from environmental factors, thereby extending their service life. Moreover, the high transparency enables the organic silicone film to effectively transmit light, which can ensure the photoelectric performance of perovskite cells. Although organic silicone materials have excellent properties in many aspects, their low refractive index will lead to a decrease in the effective utilization rate of light, thereby reducing the conversion rate of electrical energy. Organic silicon materials usually have a high water vapor permeability, which may cause moisture to enter the perovskite battery through the film layer, which will cause the degradation of the perovskite material, affect the battery performance, and even cause failure. Patent CN111205815A prepared a sealant composition with UV-curable functional organic polysiloxane as the main component. However, it can be seen from the performance data of its specific embodiment that its water vapor permeability is still relatively high.
[0004] Therefore, it has become an urgent need in the industry to develop a new type of silicone encapsulation film that can effectively resist moisture intrusion, extend the service life of perovskite batteries, and improve the optical performance of batteries. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a liquid encapsulation adhesive, and the encapsulation adhesive film after curing has excellent light transmittance, stability, mechanical strength and water vapor barrier properties, which can effectively extend the service life of the perovskite battery.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a liquid packaging adhesive, wherein the liquid packaging adhesive comprises an A component and a B component.
[0008] The component A comprises, by weight, 5-20 parts of acrylate-modified polybutadiene, 30-50 parts of vinyl silicone oil, 1-5 parts of vinyl silicone resin, 0.1-0.5 parts of catalyst and 1-5 parts of coupling agent.
[0009] The component B comprises, by weight, 5-20 parts of acrylate-modified polybutadiene, 30-50 parts of vinyl silicone oil, 1-5 parts of vinyl silicone resin, 1-10 parts of crosslinking agent, 0.1-1 parts of chain extender and 0.01-0.5 parts of inhibitor.
[0010] The amount of acrylate-modified polybutadiene is 5-20 parts, for example, 5 parts, 8 parts, 10 parts, 13 parts, 15 parts, 18 parts or 20 parts.
[0011] The vinyl silicone oil is contained in an amount of 30-50 parts, for example, 30 parts, 35 parts, 40 parts, 45 parts or 50 parts.
[0012] Among them, the vinyl silicone resin is 1-5 parts, for example, it can be 1 part, 2 parts, 3 parts, 4 parts or 5 parts.
[0013] The catalyst is present in an amount of 0.1-0.5 parts, for example, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts or 0.5 parts.
[0014] The coupling agent is 1-5 parts, for example, 1 part, 2 parts, 3 parts, 4 parts or 5 parts.
[0015] The cross-linking agent is 1-10 parts, for example, 1 part, 2 parts, 4 parts, 6 parts, 8 parts or 10 parts.
[0016] The chain extender is 0.1-1 part, for example, 0.1 part, 0.2 part, 0.4 part, 0.6 part, 0.8 part or 1 part.
[0017] The inhibitor is present in an amount of 0.01-0.5 parts, for example, 0.01 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts or 0.5 parts.
[0018] The present invention adopts vinyl silicone resin as the main resin, wherein the Si-O-Si structure provides the colloid with good heat resistance, weather resistance and chemical corrosion resistance, and effectively improves the stability of the colloid; the acrylate-modified polybutadiene is adopted to further enhance the water vapor barrier and refractive index of the colloid; the vinyl silicone oil is adopted to enhance the flexibility and elasticity of the colloid, so that the perovskite battery assembly has good buffering capacity during lamination, and the perovskite material is prevented from being damaged by large stress; the crosslinking agent and the vinyl silicone resin are synergistically compounded to enhance the tensile strength and tear resistance of the colloid; the addition of the chain extender extends the organic silicon molecular chain, and improves the elongation at break and adhesion of the colloid; the addition of the coupling agent enhances the adhesion of the colloid, so that the interface between the colloid and the glass substrate can be 100% destroyed; the compounding of the catalyst and the inhibitor extends the operating time of the colloid at room temperature, which is more conducive to industrial application.
[0019] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0020] Preferably, the raw materials for preparing the acrylic acid-modified polybutadiene include acryloyl chloride compounds, polyolefin polyols and acid-binding agents.
[0021] Preferably, the method for preparing the acrylic acid-modified polybutadiene comprises the following steps:
[0022] After the polyolefin polyol and the acid binding agent are mixed, an acryloyl chloride compound is added to react, and after the reaction is completed, acrylic acid-modified polybutadiene is obtained.
[0023] Preferably, the reaction time is 1-12 h, for example, 1 h, 2 h, 4 h, 6 h, 8 h, 10 h or 12 h.
[0024] Preferably, the reaction temperature is 55-65°C, for example, 55°C, 58°C, 60°C, 62°C or 65°C.
[0025] Preferably, after the reaction is completed, filtering and drying steps are also included.
[0026] Preferably, the acryloyl chloride compound includes any one of acryloyl chloride, methacryloyl chloride, ethylacryloyl chloride or propylacryloyl chloride, or a combination of at least two thereof.
[0027] Preferably, the polyolefin polyol comprises hydroxyl-terminated polybutadiene and / or hydrogenated hydroxyl-terminated polybutadiene.
[0028] Preferably, the acid binding agent comprises any one of anhydrous sodium carbonate, anhydrous potassium carbonate, anhydrous calcium carbonate, pyridine or triethylamine, or a combination of at least two thereof.
[0029] Preferably, the structure of the acrylic acid-modified polybutadiene is as shown in formula (1) or formula (2):
[0030]
[0031] Wherein, a is selected from 0-1, b is selected from 0-1, c is selected from 0-1, n is selected from an integer in the range of 0-100, and R is selected from hydrogen, methyl, ethyl or propyl.
[0032] Preferably, the vinyl-containing silicone oil includes any one of vinyl-terminated dimethylpolysiloxane, vinyl-terminated dimethylmethylvinylpolysiloxane or methyl-terminated polyvinylmethyldimethylsiloxane, or a combination of at least two thereof.
[0033] Preferably, the mass percentage of vinyl in the vinyl-containing silicone oil is 0.01%-5%, for example, it can be 0.01%, 1%, 2%, 3%, 4% or 5%.
[0034] Preferably, the viscosity of the vinyl-containing silicone oil at 25° C. is 100-100000 mPa·s, for example, it may be 100 mPa·s, 500 mPa·s, 1000 mPa·s, 5000 mPa·s, 10000 mPa·s, 50000 mPa·s or 100000 mPa·s.
[0035] Preferably, the vinyl silicone resin comprises vinyl MQ silicone resin.
[0036] Preferably, the ratio of M to Q in the vinyl MQ silicone resin is (0.5-1.2):1, for example, it can be 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1 or 1.2:1.
[0037] Preferably, the crosslinking agent comprises any one of trimethylsiloxane-terminated dimethylmethylhydrogenpolysiloxane, hydrogen-terminated dimethylpolysiloxane or hydrogen-terminated dimethylmethylhydrogenpolysiloxane, or a combination of at least two thereof.
[0038] Preferably, the mass percentage of hydrogen atoms in the cross-linking agent is 0.01%-2%, for example, it can be 0.01%, 0.1%, 0.5%, 1%, 1.5% or 2%.
[0039] Preferably, the viscosity of the cross-linking agent at 25° C. is 10-1000 mPa·s, for example, 10 mPa·s, 50 mPa·s, 100 mPa·s, 500 mPa·s or 1000 mPa·s.
[0040] Preferably, the chain extender comprises hydrogen terminated dimethylpolysiloxane.
[0041] Preferably, the mass percentage of hydrogen atoms in the chain extender is 0.01%-1%, for example, it can be 0.01%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8% or 1%.
[0042] Preferably, the viscosity of the chain extender at 25° C. is 5-1000 mPa·s, for example, 5 mPa·s, 50 mPa·s, 100 mPa·s, 500 mPa·s or 1000 mPa·s.
[0043] Preferably, the coupling agent is a silane coupling agent.
[0044] Preferably, the structure of the silane coupling agent is R1(CH2) x Si(OR2)3.
[0045] Wherein, x is an integer from 0 to 3, R1 is selected from methyl, vinyl, acryloyloxy, methacryloyloxy, amino, epoxy, mercapto or isocyanate, and R2 is methyl or ethyl.
[0046] Preferably, the catalyst is a platinum catalyst.
[0047] Preferably, the platinum catalyst comprises any one or a combination of at least two of chloroplatinic acid, Karstedt catalyst, Ashby catalyst, Speier catalyst or Lamoreaux catalyst.
[0048] Preferably, the inhibitor comprises any one of maleate, fumarate, acetylene, phenylacetylene, butynedioate, 2-vinyl isopropanol, 2-ethynylbut-2-ol, 3-phenyl-1-butene-3-ol, 1-ethynyl-1-cyclopentanol, 2-methyl-3-butyn-2-ol, 1-ethynyl-1-cyclohexanol, vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, vinyltri(2-methoxyethoxy)silane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane or 3-acryloxypropyltrimethoxysilane, or a combination of at least two thereof.
[0049] Preferably, the viscosity of the liquid packaging adhesive at 25° C. is 1000-50000 mPa·s, for example, 1000 mPa·s, 5000 mPa·s, 10000 mPa·s or 50000 mPa·s.
[0050] In a second aspect, the present invention provides a method for preparing the liquid encapsulating adhesive as described in the first aspect, characterized in that the preparation method comprises the following steps:
[0051] Preparation of component A: Mixing acrylate-modified polybutadiene, vinyl-containing silicone oil, vinyl silicone resin, coupling agent and catalyst to obtain the component A.
[0052] Preparation of component B: Mixing acrylate-modified polybutadiene, vinyl-containing silicone oil, vinyl silicone resin, a crosslinking agent, a chain extender and an inhibitor to obtain the component B.
[0053] In a third aspect, the present invention provides a packaging adhesive film, which is obtained by mixing component A and component B of the liquid packaging adhesive described in the first aspect, degassing, and then curing.
[0054] Preferably, the mixing ratio of component A to component B is 1:(0.9-1.1), for example, it can be 1:0.9, 1:1 or 1:1.1.
[0055] Preferably, the curing time is 15-25 min, for example, 15 min, 17 min, 20 min, 22 min or 25 min.
[0056] Preferably, the curing temperature is 90-110°C, for example, 90°C, 95°C, 100°C, 105°C or 110°C.
[0057] In a fourth aspect, the present invention provides an application of the encapsulation film as described in the third aspect in perovskite battery encapsulation technology.
[0058] Compared with the prior art, the present invention has at least the following beneficial effects:
[0059] (1) The present invention adopts vinyl silicone resin as the main resin, wherein the Si-O-Si structure provides the colloid with good heat resistance, weather resistance and chemical corrosion resistance, effectively improving the stability of the colloid; the acrylate-modified polybutadiene is used to further enhance the water vapor barrier and refractive index of the colloid; the vinyl silicone oil is used to improve the flexibility and elasticity of the colloid, so that the perovskite battery assembly has good buffering capacity during lamination, thereby avoiding damage to the perovskite material due to large stress.
[0060] (2) The crosslinking agent and the vinyl silicone resin in the present invention are synergistically compounded to enhance the tensile strength and tear resistance of the colloid; the addition of the chain extender extends the silicone molecular chain, thereby improving the elongation at break and adhesion of the colloid; the addition of the coupling agent enhances the adhesion of the colloid, thereby achieving 100% interface destruction between the colloid and the glass substrate; the compounding of the catalyst and the inhibitor extends the operating time of the colloid at room temperature, which is more conducive to industrial application.
[0061] (3) Specifically, the liquid encapsulating adhesive prepared by the present invention has a viscosity of 1000-50000 mPa· at 25°C, a colorless and transparent appearance, a refractive index of more than 1.45%, and a curing shrinkage of ≤0.5%; the encapsulating adhesive film obtained after the liquid encapsulating adhesive is cured has a light transmittance of ≥95%, an elongation at break of ≥400%, and a volume resistivity of ≥1.0×10 15 Ω·cm, water vapor transmission value ≤20g / m 2 , peeling force / glass ≥40N / cm, elastic modulus up to 1-3N / mm 2 , Shore hardness is 10-30HA; UV aging resistance (UV wavelength 290nm-400nm, 60kWh / m 2 ), high temperature and humidity aging resistance (85℃, 85%RH, 1000h), high temperature aging resistance (120℃, 48h) performance: yellowing index Δb<0.5, light transmittance ≥93%, peel force / glass ≥30N / cm, elongation at break ≥300%. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 This is the infrared spectrum of acrylate-modified polybutadiene of formula (2). DETAILED DESCRIPTION
[0063] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0064] In the following specific implementation of the present invention, the specific information of the materials used is as follows:
[0065] 1. Acrylate modified polybutadiene, homemade;
[0066] 2. Vinyl silicone oil:
[0067] A composition in which Hesheng Silicone HS-3500 (the mass percentage of vinyl is 0.2%, and the viscosity at 25°C is 3500mPa·s) and Hesheng Silicone HS-60000 (the mass percentage of vinyl is 0.09%, and the viscosity at 25°C is 60000mPa·s) are mixed in a ratio of 1:1.
[0068] 3. Vinyl silicone resin, vinyl MQ resin SH-5202N, purchased from Hubei Longsheng Sihai New Materials, the ratio of M to Q is 0.8:1;
[0069] 4. Cross-linking agent, RH-H802, purchased from Zhejiang Runhe (mass percentage of hydrogen atoms is 0.82%, viscosity at 25°C is 110 mPa·s);
[0070] 5. Chain extender, RH-H45, purchased from Zhejiang Runhe (mass percentage of hydrogen atoms is 0.12%, viscosity at 25°C is 20 mPa·s);
[0071] 6. Coupling agent, KBM-1003, purchased from Shin-Etsu, Japan;
[0072] 7. Inhibitor, ME75, purchased from Caiyuan Organic Silicon Materials, Dongguan City;
[0073] 8. Catalyst: Karstedt platinum catalyst, PT5000, purchased from Guangzhou Xiyi Chemical.
[0074] In the following specific embodiments of the present invention, the preparation method of acrylic acid-modified polybutadiene used comprises the following steps:
[0075] 500 g of hydrogenated hydroxy-terminated polybutadiene and 50 g of triethylamine were added to a reaction kettle and mechanically stirred at room temperature at a speed of 300 r / min for 30 min. Then, 56 g of acryloyl chloride was added and continued to be stirred. The reaction temperature was 60° C. and the reaction time was 8 h to obtain a reactant. After cooling to room temperature, 500 g of deionized water was added. After the reactant was separated into layers, the water was poured out and filtered. The filtered product was placed in a vacuum oven at 80° C. and evacuated for 2 h. The vacuum degree was -0.1 MPa to obtain acrylate-modified polybutadiene (Formula (2)) with a viscosity of 3000 mPa·s.
[0076]
[0077] Among them, a is 0.6, b is 0.2, c is 0.2, n is 30, and R is hydrogen.
[0078] Example 1
[0079] A liquid packaging adhesive, the liquid packaging adhesive comprising component A and component B;
[0080] The component A comprises, by weight, 5 parts of acrylate-modified polybutadiene, 40.3 parts of vinyl silicone oil, 2.5 parts of vinyl silicone resin, 0.2 parts of catalyst and 2 parts of coupling agent;
[0081] The B component comprises, by weight, 5 parts of acrylate-modified polybutadiene, 39.7 parts of vinyl silicone oil, 2.5 parts of vinyl silicone resin, 2 parts of crosslinking agent, 0.7 parts of chain extender and 0.1 parts of inhibitor;
[0082] The preparation method of the encapsulation film is as follows:
[0083] (1) preparing component A: mixing 5 parts of acrylate-modified polybutadiene, 40.3 parts of vinyl silicone oil, 2.5 parts of vinyl silicone resin, 2 parts of silane coupling agent and 0.2 parts of platinum catalyst to obtain the component A;
[0084] Preparation of component B: 5 parts of acrylate-modified polybutadiene, 39.7 parts of vinyl silicone oil, 2.5 parts of vinyl silicone resin, 2 parts of crosslinking agent, 0.7 parts of chain extender and 0.1 parts of inhibitor are mixed to obtain the component B;
[0085] (2) The component A and the component B are fully mixed in a mass ratio of 1:1, and degassing treatment is performed after gluing, and thermal curing is performed at 100° C. for 20 minutes to obtain the encapsulation adhesive film.
[0086] Example 2
[0087] A liquid packaging adhesive, the liquid packaging adhesive comprising component A and component B;
[0088] The component A comprises, by weight, 5 parts of acrylate-modified polybutadiene, 34.8 parts of vinyl silicone oil, 5 parts of vinyl silicone resin, 0.2 parts of catalyst and 5 parts of coupling agent;
[0089] The B component includes, by weight, 5 parts of acrylate-modified polybutadiene, 29.2 parts of vinyl silicone oil, 5 parts of vinyl silicone resin, 10 parts of a crosslinking agent, 0.3 parts of a chain extender and 0.5 parts of an inhibitor.
[0090] The preparation method of the encapsulation film is as follows:
[0091] (1) preparing component A: mixing 5 parts of acrylate-modified polybutadiene, 34.8 parts of vinyl silicone oil, 5 parts of vinyl silicone resin, 5 parts of silane coupling agent and 0.2 parts of platinum catalyst to obtain the component A;
[0092] Preparation of component B: 5 parts of acrylate-modified polybutadiene, 29.2 parts of vinyl silicone oil, 5 parts of vinyl silicone resin, 10 parts of a crosslinking agent, 0.3 parts of a chain extender and 0.5 parts of an inhibitor are mixed to obtain the component B;
[0093] (2) The component A and the component B are fully mixed in a mass ratio of 1:1, and degassing treatment is performed after gluing, and thermal curing is performed at 100° C. for 20 minutes to obtain the encapsulation adhesive film.
[0094] Example 3
[0095] A liquid packaging adhesive, the liquid packaging adhesive comprising component A and component B;
[0096] The component A comprises, by weight, 10 parts of acrylate-modified polybutadiene, 33 parts of vinyl silicone oil, 2.5 parts of vinyl silicone resin, 0.5 parts of catalyst and 4 parts of coupling agent;
[0097] The B component includes, by weight, 10 parts of acrylate-modified polybutadiene, 32 parts of vinyl silicone oil, 2.5 parts of vinyl silicone resin, 5 parts of crosslinking agent, 0.2 parts of chain extender and 0.3 parts of inhibitor.
[0098] The preparation method of the encapsulation film is as follows:
[0099] (1) preparing component A: mixing 10 parts of acrylate-modified polybutadiene, 33 parts of vinyl silicone oil, 2.5 parts of vinyl silicone resin, 4 parts of silane coupling agent and 0.5 parts of platinum catalyst to obtain the component A;
[0100] Preparation of component B: 10 parts of acrylate-modified polybutadiene, 32 parts of vinyl silicone oil, 2.5 parts of vinyl silicone resin, 5 parts of crosslinking agent, 0.2 parts of chain extender and 0.3 parts of inhibitor are mixed to obtain the component B;
[0101] (2) The component A and the component B are fully mixed in a mass ratio of 1:1, and degassing treatment is performed after gluing, and thermal curing is performed at 100° C. for 20 minutes to obtain the encapsulation adhesive film.
[0102] Example 4
[0103] A liquid packaging adhesive, the liquid packaging adhesive comprising component A and component B;
[0104] The component A comprises, by weight, 15 parts of acrylate-modified polybutadiene, 29.5 parts of vinyl silicone oil, 2 parts of vinyl silicone resin, 0.5 parts of catalyst and 3 parts of coupling agent;
[0105] The B component includes, by weight, 15 parts of acrylate-modified polybutadiene, 27.5 parts of vinyl silicone oil, 2 parts of vinyl silicone resin, 5 parts of crosslinking agent, 0.4 parts of chain extender and 0.1 parts of inhibitor.
[0106] The preparation method of the encapsulation film is as follows:
[0107] (1) preparing component A: mixing 15 parts of acrylate-modified polybutadiene, 29.5 parts of vinyl silicone oil, 2 parts of vinyl silicone resin, 3 parts of silane coupling agent and 0.5 parts of platinum catalyst to obtain the component A;
[0108] Preparation of component B: 15 parts of acrylate-modified polybutadiene, 27.5 parts of vinyl silicone oil, 2 parts of vinyl silicone resin, 5 parts of crosslinking agent, 0.4 parts of chain extender and 0.1 parts of inhibitor are mixed to obtain the component B;
[0109] (2) The component A and the component B are fully mixed in a mass ratio of 1:1, and degassing treatment is performed after gluing, and thermal curing is performed at 100° C. for 20 minutes to obtain the encapsulation adhesive film.
[0110] Example 5
[0111] A liquid packaging adhesive, the liquid packaging adhesive comprising component A and component B;
[0112] The component A comprises, by weight, 5 parts of acrylate-modified polybutadiene, 34.8 parts of vinyl silicone oil, 5 parts of vinyl silicone resin, 0.2 parts of catalyst and 5 parts of coupling agent;
[0113] The B component includes, by weight, 5 parts of acrylate-modified polybutadiene, 29.2 parts of vinyl silicone oil, 5 parts of vinyl silicone resin, 10 parts of a crosslinking agent, 0.3 parts of a chain extender and 0.5 parts of an inhibitor.
[0114] The preparation method of the encapsulation film is as follows:
[0115] (1) preparing component A: mixing 5 parts of acrylate-modified polybutadiene, 34.8 parts of vinyl silicone oil, 5 parts of vinyl silicone resin, 5 parts of silane coupling agent and 0.2 parts of platinum catalyst to obtain the component A;
[0116] Preparation of component B: 5 parts of acrylate-modified polybutadiene, 29.2 parts of vinyl silicone oil, 5 parts of vinyl silicone resin, 10 parts of a crosslinking agent, 0.3 parts of a chain extender and 0.5 parts of an inhibitor are mixed to obtain the component B;
[0117] (2) The component A and the component B are fully mixed in a mass ratio of 1:1, and degassing treatment is performed after gluing, and thermal curing is performed at 100° C. for 20 minutes to obtain the encapsulation adhesive film.
[0118] Comparative Example 1
[0119] A liquid packaging adhesive, the liquid packaging adhesive comprising component A and component B;
[0120] The component A comprises, by weight, 45.3 parts of vinyl silicone oil, 2.5 parts of vinyl silicone resin, 0.2 parts of catalyst and 2 parts of coupling agent;
[0121] The B component includes, by weight, 44.7 parts of vinyl silicone oil, 2.5 parts of vinyl silicone resin, 2 parts of crosslinking agent, 0.7 parts of chain extender and 0.1 parts of inhibitor.
[0122] The preparation method of the encapsulation film is as follows:
[0123] (1) preparing component A: mixing 45.3 parts of vinyl silicone oil, 2.5 parts of vinyl silicone resin, 2 parts of silane coupling agent and 0.2 parts of platinum catalyst to obtain the component A;
[0124] Preparation of component B: 44.7 parts of vinyl silicone oil, 2.5 parts of vinyl silicone resin, 2 parts of crosslinking agent, 0.7 parts of chain extender and 0.1 parts of inhibitor are mixed to obtain the component B;
[0125] (2) The component A and the component B are fully mixed in a mass ratio of 1:1, and degassing treatment is performed after gluing, and thermal curing is performed at 100° C. for 20 minutes to obtain the encapsulation adhesive film.
[0126] Comparative Example 2
[0127] A liquid packaging adhesive, the liquid packaging adhesive comprising component A and component B;
[0128] The component A comprises, by weight, 5 parts of acrylate-modified polybutadiene, 40.3 parts of vinyl silicone oil, 2.5 parts of vinyl silicone resin, 0.2 parts of catalyst and 2 parts of coupling agent;
[0129] The B component includes, by weight, 5 parts of acrylate-modified polybutadiene, 39.7 parts of vinyl silicone oil, 2.5 parts of vinyl silicone resin, 2 parts of crosslinking agent, 0.7 parts of chain extender and 0.1 parts of inhibitor.
[0130] The preparation method of the encapsulation film is as follows:
[0131] (1) preparing component A: mixing 5 parts of acrylate-modified polybutadiene, 40.3 parts of vinyl silicone oil, 2.5 parts of vinyl silicone resin, 2 parts of silane coupling agent and 0.2 parts of platinum catalyst to obtain the component A;
[0132] Preparation of component B: 5 parts of acrylate-modified polybutadiene, 39.7 parts of vinyl silicone oil, 2.5 parts of vinyl silicone resin, 2 parts of crosslinking agent, 0.7 parts of chain extender and 0.1 parts of inhibitor are mixed to obtain the component B;
[0133] (2) The component A and the component B are fully mixed at a mass ratio of 1:1.5, and degassing treatment is performed after gluing, and thermal curing is performed at 100° C. for 20 minutes to obtain the encapsulation adhesive film.
[0134] Comparative Example 3
[0135] A liquid packaging adhesive, the liquid packaging adhesive comprising component A and component B;
[0136] The component A comprises, by weight, 5 parts of acrylate-modified polybutadiene, 40.3 parts of vinyl silicone oil, 2.5 parts of vinyl silicone resin, 0.2 parts of catalyst and 2 parts of coupling agent;
[0137] The B component includes, by weight, 5 parts of acrylate-modified polybutadiene, 39.7 parts of vinyl silicone oil, 2.5 parts of vinyl silicone resin, 2 parts of crosslinking agent, 0.7 parts of chain extender and 0.1 parts of inhibitor.
[0138] The preparation method of the encapsulation film is as follows:
[0139] (1) preparing component A: mixing 5 parts of acrylate-modified polybutadiene, 40.3 parts of vinyl silicone oil, 2.5 parts of vinyl silicone resin, 2 parts of silane coupling agent and 0.2 parts of platinum catalyst to obtain the component A;
[0140] Preparation of component B: 5 parts of acrylate-modified polybutadiene, 39.7 parts of vinyl silicone oil, 2.5 parts of vinyl silicone resin, 2 parts of crosslinking agent, 0.7 parts of chain extender and 0.1 parts of inhibitor are mixed to obtain the component B;
[0141] (2) The component A and the component B are fully mixed at a mass ratio of 1:0.5, and degassing treatment is performed after gluing, and thermal curing is performed at 100° C. for 20 minutes to obtain the encapsulation adhesive film.
[0142] Test Method
[0143] (1) The viscosity, light transmittance and refractive index of the liquid encapsulants prepared in Examples 1-5 and Comparative Examples 1-3 were tested:
[0144] Viscosity: The test is carried out in accordance with the GB / T 22235-2008 standard;
[0145] Light transmittance: The test is carried out in accordance with the GB / T 2410-2008 standard, with a wavelength of 600-1000nm;
[0146] Refractive index: The test is carried out in accordance with the GB / T 39691-2020 standard;
[0147] Appearance: Visually inspect the colloid color.
[0148] (2) The liquid encapsulating adhesives prepared in Examples 1-5 and Comparative Examples 1-3 were cured at 100° C. for 20 min to obtain encapsulating adhesive films, and the encapsulating adhesive films were tested for shrinkage, light transmittance, hardness, volume resistivity, elongation at break, peel strength (with glass), elastic modulus, yellowing performance, high temperature and high humidity resistance, and UV aging resistance:
[0149] Curing shrinkage: The test is carried out in accordance with the ISO 4216:2021 standard;
[0150] Light transmittance: The test is carried out in accordance with the GB / T 2410-2008 standard, with a wavelength of 600-1000nm;
[0151] Hardness: The test is carried out in accordance with the GB / T 2411-2008 standard;
[0152] Volume resistivity: The test is carried out in accordance with the GB / T 1410-2006 standard;
[0153] Elongation at break: The test is carried out in accordance with the GB / T 528-2009 standard;
[0154] Peel force / glass: The test is carried out in accordance with GB / T 2790-1995 standard;
[0155] Elastic modulus: The test is carried out in accordance with the standard "HGT 3321-2012";
[0156] Yellowing index Δb (UV60KWh): Tested according to the test method provided by ASTM E313-2010, with the test temperature at 85°C and relative humidity at 85%;
[0157] Water vapor transmission value (g / m 2 day)1mm: The test is carried out in accordance with the standard "GB 1037-88";
[0158] UV aging resistance (appearance): wavelength is 290nm-400nm, UV60KWh. After UV aging test, visually inspect the film appearance color change and whether there is debonding;
[0159] UV aging resistance (light transmittance): The test is carried out in accordance with the GB / T 2410-2008 standard, with a wavelength of 600-1000nm;
[0160] UV aging resistance (Δb(UV60KWh)): Tested according to the test method provided in ASTM E313-2010, with the test temperature at 85°C and relative humidity at 85%;
[0161] High temperature and high humidity aging resistance (appearance): After high temperature and high humidity aging test, the experimental temperature is 85℃, relative humidity is 85%, 1000h, visually observe the color change of the film appearance and whether there is debonding phenomenon;
[0162] High temperature and high humidity aging resistance (light transmittance): The test is carried out in accordance with the GB / T 2410-2008 standard, with a wavelength of 600-1000nm;
[0163] High temperature aging resistance (appearance): After high temperature aging test, 120℃, 48h, visually inspect the color change of the film and whether there is debonding;
[0164] High temperature aging resistance (light transmittance): The test is carried out in accordance with the GB / T 2410-2008 standard, with a wavelength of 600-1000nm.
[0165] Test Results
[0166] The performance tests were conducted on the liquid encapsulating adhesives prepared in Examples 1-5 and Comparative Examples 1-3 and the encapsulating adhesive films after curing. The results are shown in Table 1-2.
[0167] Table 1
[0168]
[0169]
[0170]
[0171] Table 2
[0172]
[0173]
[0174]
[0175] The test results show that:
[0176] (1) It can be seen from Examples 1 to 5 that the liquid encapsulating adhesive prepared by the present invention has a viscosity of 1000-50000 mPa at 25°C, a colorless and transparent appearance, a refractive index of more than 1.45%, and a curing shrinkage of ≤0.5%; the encapsulating adhesive film obtained after the liquid encapsulating adhesive is cured has a light transmittance of ≥95%, an elongation at break of ≥400%, and a volume resistivity of ≥1.0×10 15 Ω·cm, water vapor transmission value ≤20g / m 2 , peeling force / glass ≥40N / cm, elastic modulus up to 1-3N / mm 2, Shore hardness is 10-30HA; UV aging resistance (UV wavelength 290nm-400nm, 60kWh / m 2 ), high temperature and high humidity aging resistance (85℃, 85%RH, 1000h), high temperature aging resistance (120℃, 48h) performance: yellowing index Δb<0.5, transmittance ≥93%, peel force / glass ≥30N / cm, elongation at break ≥300%, can effectively resist moisture intrusion and improve the optical properties of the film.
[0177] (2) It can be seen from Example 1 and Comparative Example 1 that the present invention can achieve better water vapor barrier properties by adding homemade acrylic modified polybutadiene to the liquid encapsulation glue to ensure long-term and efficient operation of the photovoltaic module, and also improve the refractive index, which can improve the efficiency of the perovskite cell in using sunlight.
[0178] (3) It can be seen from Example 1 and Comparative Examples 2-3 that the operation of mixing the liquid encapsulating adhesive component A and component B prepared by the present invention in a prescribed ratio is simple and conducive to industrialization. However, when the prescribed ratio is not followed, excessive component A may result in incomplete crosslinking, an increased water vapor permeability value, and debonding after aging. Excessive component B may result in excessive crosslinking agent, hardening of the adhesive film, an increased water vapor permeability value, and debonding after aging, and the technical effect of the adhesive film blocking water vapor cannot be achieved.
[0179] Figure 1 The infrared spectra of hydrogenated hydroxyl-terminated polybutadiene and acrylate-modified polybutadiene of formula (2) are shown in Figure 1. The acrylate-modified polybutadiene has a higher infrared spectroscopy wavelength at 3300 cm-1 than the hydrogenated hydroxyl-terminated polybutadiene. -1 The -OH absorption peak disappears at 1730 cm -1 There is a strong absorption peak of C=O at 1200cm -1 There is a strong absorption peak of COC at 1630cm -1 A C=C absorption peak appears at , indicating successful surface acryloyloxy grafting.
[0180] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A liquid packaging adhesive, characterized in that: The liquid packaging glue comprises component A and component B; The component A comprises, by weight, 5-20 parts of acrylate-modified polybutadiene, 30-50 parts of vinyl silicone oil, 1-5 parts of vinyl silicone resin, 0.1-0.5 parts of catalyst and 1-5 parts of coupling agent; The component B comprises, by weight, 5-20 parts of acrylate-modified polybutadiene, 30-50 parts of vinyl silicone oil, 1-5 parts of vinyl silicone resin, 1-10 parts of crosslinking agent, 0.1-1 parts of chain extender and 0.01-0.5 parts of inhibitor.
2. The liquid packaging adhesive according to claim 1, characterized in that: The raw materials for preparing the acrylic acid-modified polybutadiene include acryloyl chloride compounds, polyolefin polyols and acid-binding agents; Preferably, the method for preparing the acrylic acid-modified polybutadiene comprises the following steps: After mixing the polyolefin polyol and the acid binding agent, adding an acryloyl chloride compound to react, and obtaining acrylic acid-modified polybutadiene after the reaction is completed; Preferably, the reaction time is 1-12h; Preferably, the reaction temperature is 55-65°C; Preferably, after the reaction is completed, filtering and drying steps are also included; Preferably, the acryloyl chloride compound includes any one of acryloyl chloride, methacryloyl chloride, ethylacryloyl chloride or propylacryloyl chloride, or a combination of at least two thereof; Preferably, the polyolefin polyol comprises hydroxyl-terminated polybutadiene and / or hydrogenated hydroxyl-terminated polybutadiene; Preferably, the acid binding agent comprises any one of anhydrous sodium carbonate, anhydrous potassium carbonate, anhydrous calcium carbonate, pyridine or triethylamine, or a combination of at least two thereof; Preferably, the structure of the acrylic acid-modified polybutadiene is as shown in formula (1) or formula (2): Wherein, a is selected from 0-1, b is selected from 0-1, c is selected from 0-1, n is selected from an integer in the range of 0-100, and R is selected from hydrogen, methyl, ethyl or propyl.
3. The liquid packaging adhesive according to claim 1 or 2, characterized in that: The vinyl-containing silicone oil includes any one or a combination of at least two of vinyl-terminated dimethylpolysiloxane, vinyl-terminated dimethylmethylvinylpolysiloxane or methyl-terminated polyvinylmethyldimethylsiloxane; Preferably, the mass percentage of vinyl in the vinyl-containing silicone oil is 0.01%-5%; Preferably, the viscosity of the vinyl silicone oil at 25° C. is 100-100000 mPa·s; Preferably, the vinyl silicone resin comprises vinyl MQ silicone resin; Preferably, the ratio of M to Q in the vinyl MQ silicone resin is (0.5-1.2):
1.
4. The liquid packaging adhesive according to any one of claims 1 to 3, characterized in that: The crosslinking agent includes any one of trimethylsiloxane-terminated dimethylmethylhydrogenpolysiloxane, hydrogen-terminated dimethylpolysiloxane or hydrogen-terminated dimethylmethylhydrogenpolysiloxane, or a combination of at least two thereof; Preferably, the mass percentage of hydrogen atoms in the cross-linking agent is 0.01%-2%; Preferably, the viscosity of the cross-linking agent at 25° C. is 10-1000 mPa·s; Preferably, the chain extender comprises hydrogen terminated dimethylpolysiloxane; Preferably, the mass percentage of hydrogen atoms in the chain extender is 0.01%-1%; Preferably, the viscosity of the chain extender at 25° C. is 5-1000 mPa·s.
5. The liquid packaging adhesive according to any one of claims 1 to 4, characterized in that: The coupling agent is a silane coupling agent; Preferably, the structure of the silane coupling agent is R1(CH2) x Si(OR2)3; Wherein, x is an integer from 0 to 3, R1 is selected from methyl, vinyl, acryloyloxy, methacryloyloxy, amino, epoxy, mercapto or isocyanate, and R2 is methyl or ethyl.
6. The liquid packaging adhesive according to any one of claims 1 to 5, characterized in that: The catalyst is a platinum catalyst; Preferably, the platinum catalyst comprises any one or a combination of at least two of chloroplatinic acid, Karstedt catalyst, Ashby catalyst, Speier catalyst or Lamoreaux catalyst; Preferably, the inhibitor comprises any one of maleate, fumarate, acetylene, phenylacetylene, butynedioate, 2-vinyl isopropanol, 2-ethynylbut-2-ol, 3-phenyl-1-butene-3-ol, 1-ethynyl-1-cyclopentanol, 2-methyl-3-butyn-2-ol, 1-ethynyl-1-cyclohexanol, vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, vinyltri(2-methoxyethoxy)silane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropylmethyldimethoxysilane or 3-acryloxypropyltrimethoxysilane, or a combination of at least two thereof.
7. The liquid packaging adhesive according to any one of claims 1 to 6, characterized in that: The viscosity of the liquid packaging adhesive at 25° C. is 1000-50000 mPa·s.
8. A method for preparing the liquid encapsulating adhesive according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: Preparation of component A: mixing acrylate-modified polybutadiene, vinyl-containing silicone oil, vinyl silicone resin, coupling agent and catalyst to obtain component A; Preparation of component B: Mixing acrylate-modified polybutadiene, vinyl-containing silicone oil, vinyl silicone resin, a crosslinking agent, a chain extender and an inhibitor to obtain the component B.
9. A packaging film, characterized in that: The encapsulation adhesive film is obtained by mixing component A and component B of the liquid encapsulation adhesive according to any one of claims 1 to 7, degassing, and then curing; Preferably, the mixing ratio of component A to component B is 1:(0.9-1.1); Preferably, the curing time is 15-25 minutes; Preferably, the curing temperature is 90-110°C.
10. Application of the encapsulation film according to claim 9 in perovskite battery encapsulation technology.
Citation Information
Patent Citations
UV hybrid curable OLED sealant composition
CN111205815A
Ultraviolet light and moisture dual-cured composition
CN112457804A
Packaging adhesive film and preparation method and application thereof
CN116082984A
Optical packaging adhesive and preparation method thereof
CN116083046A
Organosilicon liquid optical cement capable of ink-jet printing and preparation method thereof
CN116925694A